Validation of Italian students’ self-ratings on the SSIS SEL brief scales - Cavioni, Valeria; Conte, Elisabetta; Grazzani, Ilaria; Ornaghi, Veronica; Cefai, Carmel; Anthony, Christopher; Elliott, Stephen N.; Pepe, Alessandro (Frontiers in Psychology, 2023)
Despite increasing interest in measuring social and emotional learning (SEL), there is a lack of European-validated tools for assessing the efficacy of SEL programs. The aim of this study was to validate an Italian version of the SSIS SEL Brief Scales–Student Form. Participants were 1,175 students (mean age: 11.02 years; SD: 2.42; range: 8-16 years; males: 46.8%) recruited at schools in Northern Italy. Initial confirmatory factor analysis encountered a series of challenges, implying non-convergence of the original five-factor measurement model (self-awareness, self-management, social awareness, relationship skills, and responsible decision-making) based on the CASEL competency framework established with students in the United States. Further exploratory and confirmatory analyses supported a four-factor model that remained partially invariant across gender groups. The Italian version of the SSIS SEL Brief Scales was thus shown to be an efficient measurement tool for estimating social and emotional learning in students. We discuss the implications of findings in relation to selecting valid and reliable instruments for assessing children’s and adolescents’ SEL competencies while considering the culturally-situated nature of the constructs under study.